Resolving TYK2 locus genotype-to-phenotype differences in autoimmunity - Dendrou, C; Cortes, A; Shipman, L; Evans, H; Attfield, K; Jostins, L; Barber, T; Kaur, G; Balaram Kuttikkatte, S; Leach, O; Desel, C; Faergeman, S; et al. (American Association for the Advancement of Science, 2016)
Thousands of genetic variants have been identified, which contribute to the development of complex diseases, but determining how to elucidate their biological consequences for translation into clinical benefit is challenging. Conflicting evidence regarding the functional impact of genetic variants in the tyrosine kinase 2 (TYK2) gene, which is differentially associated with common autoimmune diseases, currently obscures the potential of TYK2 as a therapeutic target. We aimed to resolve this conflict by performing genetic meta-analysis across disorders; subsequent molecular, cellular, in vivo, and structural functional follow-up; and epidemiological studies. Our data revealed a protective homozygous effect that defined a signaling optimum between autoimmunity and immunodeficiency and identified TYK2 as a potential drug target for certain common autoimmune disorders.